The Interaction of lncRNA-HEIH and lncRNA-HULC with HBXIP in Hepatitis B Patients - Lingjuan Ruan; Lifei Huang; Lilai Zhao; Qiang Wang; Xiaocheng Pan; Anmin Zhang; Qiuping Bai; Zongjun Lv (Gastroenterology Research and Practice)
Hepatitis B virus (HBV) infection is a major risk factor for the development of hepatic cirrhosis (HC) and hepatocellular carcinoma (HCC), which are associated with very high morbidity and mortality rates worldwide. Many studies have shown that long noncoding RNAs (lncRNAs) that are highly expressed in HCC (lncRNA-HEIH) and highly upregulated in liver cancer (lncRNA-HULC) have been implicated in the development and progression of hepatitis B-related HC and HCC. In this study, reverse transcription and quantitative PCR were used to detect the expression of lncRNA-HEIH and lncRNA-HULC and western blot analysis to detect the expression of hepatitis B X-interacting protein (HBXIP). RNA immunoprecipitation was used to detect the interaction of HBXIP with lncRNA-HULC and lncRNA-HEIH. The results showed that lncRNA-HEIH, lncRNA-HULC, and HBXIP were upregulated in hepatitis B patients, particularly those with hepatitis B-related HCC. Both lncRNA-HEIH and lncRNA-HULC interacted with HBXIP. These results suggest that lncRNA-HEIH and lncRNA-HULC interact with HBXIP in hepatitis B-related diseases.